Barriers and enablers for midwives using endorsement for scheduled medicines: A literature review. Issue 1 (February 2020) - Medway, Paula; Sweet, Linda; Thornton, Charlene
Abstract: Problem: There are currently 429 midwives in Australia who hold the Nursing and Midwifery Board of Australia's Endorsement for scheduled medicines for midwives. Little is known about how midwives are using the endorsement and what factors impact on its use. Objective: To critically examine the literature to discover what the barriers and enablers are for midwives to use the endorsement. Method: A search was undertaken examining literature published since 2004. Due to a lack of articles specific to midwifery, the search was widened to include literature related to similar non-medical health professions. The search was divided into two streams: accessing the Medicare Benefits Schedule and accessing the Pharmaceutical Benefits Scheme and prescribing. Twenty-six primary articles from 2009 onward met the review criteria. Findings: Although singular barriers and enablers to both streams were identified, many of the themes act as both enabler and barrier. Themes common to both the Medicare Benefits Schedule focus and the Pharmaceutical Benefits Scheme and prescribing focus are that of medical support, scope of practice, ongoing support from health care consumers and management, and endorsement processes. Barriers occur approximately three times more frequently than enablers. Conclusion: Barriers and enablers occur for various reasons including legislative, regulatory, organisational, and the individual's support for and attitude towards these roles. To overcome barriers and facilitate the success of emerging non-medical extended practice roles, significant buy-in and investment is needed across all levels of the health system. The review highlights a significant gap in knowledge about the endorsement's use in midwifery.